Caring for patients displaying agitated behaviours in the intensive care unit – A mixed-methods systematic review. Issue 4 (July 2022) - Adams, Anne Mette N.; Chamberlain, Diane; Grønkjær, Mette; Thorup, Charlotte Brun; Conroy, Tiffany
Abstract: Background: Patient agitation is common in the intensive care unit (ICU), with consequences for both patients and health professionals if not managed effectively. Research indicates that current practices may not be optimal. A comprehensive review of the evidence exploring nurses' experiences of caring for these patients is required to fully understand how nurses can be supported to take on this important role. Objectives: The aim of this study was to identify and synthesise qualitative and quantitative evidence of nurses' experiences of caring for patients displaying agitated behaviours in the adult ICU. Methods: A mixed-methods systematic review was conducted. MEDLINE, CINAHL, PsycINFO, Web of Science, Emcare, Scopus, ProQuest, and Cochrane Library were searched from database inception to July 2020 for qualitative, quantitative, and mixed-methods studies. Peer-reviewed, primary research articles and theses were considered for inclusion. A convergent integrated design, described by Joanna Briggs Institute, was utilised transforming all data into qualitative findings before categorising and synthesising to form the final integrated findings. The review protocol was registered with PROSPERO CRD42020191715. Results: Eleven studies were included in the review. Integrated findings include (i) the strain of caring for patients displaying agitated behaviours; (ii) attitudes of nurses; (iii) uncertainty around assessment and management of agitated behaviour; and (iv) lack of effective collaboration and communication with medical colleagues. Conclusions: This review describes the challenges and complexities nurses experience when caring for patients displaying agitated behaviours in the ICU. Findings indicate that nurses lack guidelines together with practical and emotional support to fulfil their role. Such initiatives are likely to improve both patient and nurse outcomes.